Tumor Necrosis Factor Alpha Levels As A Predictor Of Intussuception In Children: A Cross-Sectional Study - Mariana, Nita; Ahmadwirawan, Ahmadwirawan; Aras, Jusli; Pelupessy, Ninny Meutia; Hatta, Mochammad; Yusuf Putri, Andi Matahari Rezkya (Journal of Neonatal Surgery, 2025)
Introduction: Intussusception (IS) is a medical emergency characterized by intestinal obstruction, which can be fatal if not promptly treated. In addition, several studies have identified infectious diseases, both viral and bacterial, as common predisposing factors for IS, often leading to elevated serum levels of Tumor Necrosis Factor alpha (TNF-α). Inflammatory mediators, such as TNF-α can significantly influence gastrointestinal motility, and the resulting alterations may contribute to the development of intussusception. Hence, this study determines the relationship between TNF-α levels and intussusception in children. Methods: This cross-sectional study was performed applying simple random sampling, which examined ELISA results on the blood of intussusception patients before exploratory laparotomy milking, resection, or enterostomy at an institution from January to December 2023. Results: The sample population was 10 patients (6 males and 4 females) who underwent exploratory laparotomy milking (3) and resection/enterostomy (7). Based on the results, the TNF-α mean level was higher at 357.4032 in patients who underwent resection than 83.6314 in those who did not undergo the procedure. In addition, TNF-α levels in patients with resection/enterostomy were higher compared to those without resection with a p-value of < α (0.000 < 0.05). Conclusion: The findings showed a significant association on TNF-α levels and the incidence of intussusception. TNF-α levels in intussusception patients who underwent resection/enterostomy were higher compared to those without resection. However, further studies using larger sample sizes were still needed to assess the relationship between TNF-α levels and other diseases, with healthy children as controls.